2008
DOI: 10.1111/j.1440-1819.2008.01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex volume reduction in patients with panic disorder

Abstract: Both manual ROI tracing and optimized VBM suggest a subregion-specific pattern of ACC volume deficit in panic disorder. In addition to functional abnormalities, these results suggest that structural abnormalities of the ACC contribute to the pathophysiology of panic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 44 publications
9
67
0
1
Order By: Relevance
“…Neuroimaging studies report that chronic pain and psychiatric conditions are associated with structural and functional reorganisation of cortical structures (Asami et al, 2008;Burgmer et al, 2009;Flor et al, 2001;Hayes et al, 2012;Karl et al, 2001;Pleger et al, 2006), especially the primary somatosensory cortex (S1) in chronic pain conditions using functional magnetic resonance imaging (Vartiainen et al, 2009;Wrigley et al, 2009). Preclinical animal studies have also demonstrated that MS (maternal separation) rats exposed to WAS (water-avoidance stress) displayed an increased in activation of the S1, suggesting that stress in the adult MS rat results in enhanced sensory input to visceral noxious stimulation (Mendes-Gomes et al, 2011).…”
Section: Cortexmentioning
confidence: 99%
“…Neuroimaging studies report that chronic pain and psychiatric conditions are associated with structural and functional reorganisation of cortical structures (Asami et al, 2008;Burgmer et al, 2009;Flor et al, 2001;Hayes et al, 2012;Karl et al, 2001;Pleger et al, 2006), especially the primary somatosensory cortex (S1) in chronic pain conditions using functional magnetic resonance imaging (Vartiainen et al, 2009;Wrigley et al, 2009). Preclinical animal studies have also demonstrated that MS (maternal separation) rats exposed to WAS (water-avoidance stress) displayed an increased in activation of the S1, suggesting that stress in the adult MS rat results in enhanced sensory input to visceral noxious stimulation (Mendes-Gomes et al, 2011).…”
Section: Cortexmentioning
confidence: 99%
“…Changsheng Li proposed that social defeat stress induces the transition from acute to chronic plantar incision pain (29). Different spinal and supraspinal regions can be influenced by stress; thus, alterations to neurotransmitters within these regions play an important role in stress-pain interactions (36). For example, multiple studies have shown that the cortical structures (37), amygdala (38), periaqueductal grey (39), rostral ventromedial Medulla (28) and spinal cord dorsal horn mediate the process of stress-induced hyperalgesia.…”
Section: Figure 4 Effect Of Dexmedetomidine On the Gr Protein Expresmentioning
confidence: 99%
“…The biological approach to panic disorder and agoraphobia bases its theoretical claims on four major groups of empirical findings: (1) Studies indicating that patients with panic disorder and agoraphobia suffer from structural brain abnormalities, such as in the temporal lobe, the basal ganglia, the cingulate, and the brainstem (Asami et al, 2008;Barlow, 2004;Ham et al, 2007;Han et al, 2008;Lee et al, 2006;Stein, 2008); (2) Studies showing that genetics play a significant role in the etiology of panic disorder and agoraphobia (Chantarujikapong et al, 2001;Hettema, Neale, & Kendler, 2001;Kendler et al, 1999;Kendler et al, 2001;Nocon et al, 2008;Stein, 2008); (3) Findings obtained using the paradigm of the biological challenge, whereby panic attacks can be experimentally induced in panic disorder patients using a variety of chemical substances (e.g., sodium lactate infusion and CO 2 inhalation; see Abrams, Schruers, Cosci, & Sawtell, 2008;Barlow, 2004); (4) Research demonstrating that drug therapy is an effective intervention in the treatment of these disorders (Furukawa, Watanabe, & Churchill, 2006;Mavissakalian & Ryan, 1998;Westenberg, 1996).…”
Section: Biological Approach To Panic Disorder and Agoraphobiamentioning
confidence: 99%